2015
DOI: 10.1039/c4ob02025a
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced conjugation of tetrazoles to modified and native proteins

Abstract: Bio-orthogonal chemistry has been widely used for conjugation of polymer molecules to proteins. Here, we demonstrate the conjugation of polyethylene glycol (PEG) to bovine beta-lactoglobulin (BLG) by photo-induced cyclo-addition of tetrazole-appended PEG and allyl-modified BLG. During the course of the investigation, a significant side-reaction was found to occur for the conjugation of PEG-tetrazole to native BLG. Further exploration of the underlying chemistry reveals that the presence of a tryptophan residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…In this step, photolysis of tetrazole upon UV irradiation yields a pyrazoline cycloadduct that exhibits strong fluorescence at 495 nm ( λ max ) and serves as a useful indicator for monitoring the progress of the reaction (Supporting Information, Figure S2) . Previously, we and others have reported that in the absence of an alkene moiety, the tetrazole is capable of conjugating with other functional groups, such as the tryptophan moieties in the case of proteins . In the current work, despite targeting the conjugation towards the alkene present on βLG A‐Allyl, we could not prevent minor side‐reactions with tryptophan residues leading to the formation of di‐, and tri‐PEGylated products as confirmed by MALDI‐TOF and SDS‐PAGE analysis (Figure B).…”
Section: Figurementioning
confidence: 83%
See 1 more Smart Citation
“…In this step, photolysis of tetrazole upon UV irradiation yields a pyrazoline cycloadduct that exhibits strong fluorescence at 495 nm ( λ max ) and serves as a useful indicator for monitoring the progress of the reaction (Supporting Information, Figure S2) . Previously, we and others have reported that in the absence of an alkene moiety, the tetrazole is capable of conjugating with other functional groups, such as the tryptophan moieties in the case of proteins . In the current work, despite targeting the conjugation towards the alkene present on βLG A‐Allyl, we could not prevent minor side‐reactions with tryptophan residues leading to the formation of di‐, and tri‐PEGylated products as confirmed by MALDI‐TOF and SDS‐PAGE analysis (Figure B).…”
Section: Figurementioning
confidence: 83%
“…In the fourth and final step, PEG‐tz was conjugated to super‐charged βLG A‐Allyl via photoinduced click chemistry by irradiating the sample at 302 nm for 15 min, and the conjugation confirmed by the appearance of a fluorescence emission peak at 495 nm (Figure A). In this step, photolysis of tetrazole upon UV irradiation yields a pyrazoline cycloadduct that exhibits strong fluorescence at 495 nm ( λ max ) and serves as a useful indicator for monitoring the progress of the reaction (Supporting Information, Figure S2) . Previously, we and others have reported that in the absence of an alkene moiety, the tetrazole is capable of conjugating with other functional groups, such as the tryptophan moieties in the case of proteins .…”
Section: Figurementioning
confidence: 99%
“…Many different orthogonal bioconjugation methods with superior performance over the traditional conjugation method have been developed that involve the use of less common amino acid residues. 19,20 However, these methods have not been used for conjugating bioluminescent proteins to antibodies. Among the orthogonal conjugation methodologies, modification of the tyrosine (Tyr) residue is gaining popularity among researchers since they appear with intermediate frequency in a protein, and chemical reactivity of the Tyr phenol ring provides for several diverse reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In this step,photolysis of tetrazole upon UV irradiation yields ap yrazoline cycloadduct that exhibits strong fluorescence at 495 nm (l max )and serves as auseful indicator for monitoring the progress of the reaction (Supporting Information, Figure S2). [22] Previously, we and others have reported that in the absence of an alkene moiety,t he tetrazole is capable of conjugating with other functional groups,such as the tryptophan moieties in the case of proteins. [22] In the current work, despite targeting the conjugation towards the alkene present on bLG A-Allyl, we could not prevent minor side-reactions with tryptophan residues leading to the formation of di-, and tri-PEGylated products as confirmed by MALDI-TOF and SDS-PAGE analysis ( Figure 2B).…”
mentioning
confidence: 99%
“…[22] Previously, we and others have reported that in the absence of an alkene moiety,t he tetrazole is capable of conjugating with other functional groups,such as the tryptophan moieties in the case of proteins. [22] In the current work, despite targeting the conjugation towards the alkene present on bLG A-Allyl, we could not prevent minor side-reactions with tryptophan residues leading to the formation of di-, and tri-PEGylated products as confirmed by MALDI-TOF and SDS-PAGE analysis ( Figure 2B). When compared to the native bLG A ( Figure 2C,l ane 1), SDS-PAGEo ft he purified bLG A-PEG(+ +)and bLG A-PEG(À)showed aclear increase in their respective MW ( Figure 2C,l anes 2a nd 3, respectively).…”
mentioning
confidence: 99%